The Effect Size of Blended Learning in Mathematics Learning - Mohammad Edy Nurtamam; Baso Intang Sappaile; Sutarto; Novianty Djafri; Tomi Apra Santosa; andri kurniawan (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
This study aims to determine the effect of blended learning in mathematics learning. This type of research is quantitative research with a meta-analysis approach. The inclusion criteria are research published in 2020-2023, research must be experimental methods or quasi-experiments, research related to the influence of blended learning in mathematics learning, research comes from SINTA indexed journals, Research data is obtained through google scholar, DOAJ, Mendeley and Sinta and research has complete data to calculate the value of effect size. The results of 23 studies concluded that there was a significant influence of blended learning in mathematics learning with an average effect size value of 0.83 with a large effect category. These findings provide more accurate information about the application of blended learning in mathematics learning.